GEOECOLOGICAL PROBLEMS OF DEVELOPMENT OF NATURAL RESOURCES OF THE JIZZAKH REGION (Uzbekistan Open Conference, 2025)
In our article, we analyze the key geo-environmental problems of the Jizzakh Region. This region is located in the central part of Uzbekistan. We utilized multi-year satellite data (Landsat, Sentinel), hydrochemical observations, and GIS modeling. Our research identified the main directions of environmental degradation: secondary soil salinization, deterioration of water quality, and instability of the hydrological regime. We constructed an integrated map of geo-environmental risk. It allowed us to identify territories with high vulnerability. Based on the results, we propose recommendations for optimizing water usage, developing monitoring systems, and greening energy projects. Our conclusions can serve as a basis for regional sustainable development strategies.